First records of anacaena lutescens (Stephens, 1829) and cercyon littoralis (Gyllenhal, 1808) from Turkey (Coleoptera, Hydrophilidae) - İncekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2004)
Two Hydrophilid species (water beetles) are described as new to the Turkish fauna: Anacaena lutescens (Stephens, 1829) and Cercyon littoralis (Gyllenhal, 1808). Both were found at high altitiudes in the Black Sea region. The descriptions are supported by scanning electron microscope photographs. © 2004 Taylor & Francis Group, LLC.
Keywords: Coleoptera; Hydrophilidae; Middle East; Systematics; Turkey